IMPACT OF COVID-19 PANDEMIC ON ORGANIZATION OF PROFESSIONAL FOOTBALL LEAGUE IN NIGERIA - Ajadi, Memunat Tunrayo; Owolabi, Abdulraheem Yinus; Kayode, Falaye Elijah (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
Football is one of the major sports that contribute to the economic and social development of a community which requires effective organization. However, this study examinedÂ  impact of COVID-19 on the organization of professional football league in Nigeria. The objectives of this study were to: assess the relationship between a postponement of league and pay cut of wages of players on the organization of football league. The descriptive research design of survey type was used. The population comprised all registered players and sports administrators. A stratified and purposive sampling technique was used to select 100 respondents. Researcher-structured questionnaires were employed. The validity and reliability level of the instrument was through test re-test method using Pearson Product Moment Correlation (PPMC) and a co-efficient of 0.85r was obtained. The administration of the instrument was done by the researchers and research assistants. The data collected were analyzed using Pearson Product Moment Correlation. The result of the findings revealed that there was a significant relationship between a postponement of league and pay cut of wages and organization of professional football league in Nigeria. The study concluded that the league management and NFF should meet with other stakeholders to brainstorm the modalities on the resumption of the league in Nigeria.